Epidemiological profile of patients with Covid 19 unit of intensive care in a national Hospital of the city of Lima 2020. - Garcia Inga , Belinda Olga (2021)
Objective:  To determine the epidemiological profile of patients with Covid 19 unit of intensive care in a national Hospital of the city of Lima 2020. Material and Methods: Observational and descriptive study, the sample made up of 77 patients treated in the ICU. Results: 78.8% of the male sex, 25.9% are over 70 years old, illness time before hospitalization 6 to 10 days, the medical diagnosis of Covid pneumonia admission with 51.2%, the main symptom dyspnea 29%, the 14% with comorbidity to arterial hypertension, obesity and type 2 diabetes mellitus, 78.8% used a mechanical ventilator, multiparameter monitor and pumps, 77.5% used the pronation technique, 51.2% had an invasive procedure with endotracheal tube, central venous catheter , nasogastric tube and Foley, 20% had as a complication the pressure injury of II °, the discharge diagnosis was Covid 19 in 100%, the hospital stay of 11 to 21 days, mortality of 62%. Conclusions: the epidemiological profile of patients with Covid 19% intensive care unit is broad, affecting more those over 70 years of age, the male sex, having as main comorbidity arterial hypertension, obesity and type 2 diabetes mellitus, with a high mortality rate.